Comparison and validation of computational methods for the prediction of the compressive crush energy absorption of CFRP structures. (15th December 2020) - Rondina, Francesco; Donati, Lorenzo
Abstract: The crushing response of fiber-reinforced composite structures under compressive loading is investigated experimentally and then simulated using two damage models implemented in ESI Virtual Performance Solution explicit solver. The conventional Ladevèze continuum damage is compared to the recently implemented Waas-Pineda model, which uses non-local damage approach: virtual cracks are embedded with prescribed traction-separation laws and direct input of modal fracture energies. Initially, characterization tests of a unidirectional carbon fiber/epoxy tape are carried out to implement material card data and elementary simulations are performed for calibration. In a second stage, quasistatic crush compression of reference coupons are used for validation and numerical results are compared to experimental data in terms of specific absorbed energy. Results show that the Waas-Pineda model is easier to set up than the Ladevèze one and it also better reproduces the experimental results. The Ladevèze model underestimates the sustained crush stress since some damage modes could not be well identified from coupon testing of brittle material.